Single day mefloquine-artesunate combination in the treatment of multi-drug resistant falciparum malaria. - Luxemburger, C; ter Kuile, F; Nosten, F; Dolan, G; Bradol, J; Phaipun, L; Chongsuphajaisiddhi, T; White, N (1994)
The therapeutic efficacy and toxicity of a combination of low dose mefloquine (15 mg/kg) plus artesunate 10 mg/kg in one day (MA) was compared with the currently used regimen of high dose mefloquine (25 mg/kg) (MQ) in 552 patients with uncomplicated falciparum malaria in an area of multi-drug resistance on the Thai-Burmese border. MA gave faster clinical and parasitological responses and prevented early treatment failure; 15 patients in the MQ group (6%) were early failures (< 9 d) compared with none receiving MA (P = 0.0001). Overall failure rates by day 28 were 19% in the MA group and 24% in with MQ group (relative risk (RR) = 0.78, 95% confidence interval (CI) 0.54-1.12). In the subgroup of patients who required re-treatment, MA proved significantly more effective than MQ; failure rates were 25% and 52% respectively (RR = 0.49, 95% CI = 0.29-0.83). Treatment failures were associated with mefloquine treatment in the previous month (RR = 1.72, 95% CI = 1.09-2.70) and diarrhoea (RR = 1.55, 95% CI = 1.05-2.28). Gastrointestinal side-effects and dizziness were more likely in the MQ group. There was no evident adverse effect associated with artesunate. A single day's treatment with artesunate augments the antimalarial efficacy of mefloquine.